Germination of seeds of tomato (Solanum lycopersicum), papaya (Carica papaya L.) and passion fruit (Passiflora edulis) using organic substrates (Revista Sistemas de Producción Agroecológicos, 2018)
The quality of the seedlings is one of the most important aspects in the establishment of the vegetal material coming from the nursery, within the phytosanitary problems that are presented is the overturning, badly damaged or damping off caused by different fungi. Biochar is considered as an alternative to improve physical conditions, chemical and biological of soil, showing potential as a growth substrate. This work was carried out under a completely randomized design evaluating the growth and development in nursery of tomato (Solanum lycopersicum), papaya (Carica papaya L.) and passion fruit (Passiflora edulis). The treatments were five substrates of sowing: soil, peat and three mixtures of soil with biochar to the 10%, which was obtained at 450 °C using as raw material husks of passion fruit (Passiflora edulis), banana (Musa paradisiaca L.) and orange (Citrus sinensis). The different growth substrates did not present pathogenic fungi associated with diseases of interest such as the short-leaf disease, that affects the nursery seedlings; this can be explained by the increase in the biological activity of the substrates produced by the addition of biochar, which can generate conditions similar to those of suppressive soils. According to the results, the passionfruit and banana biochar had a deadly effect, the plants sown in the soil mixture with orange biochar presented a statistically similar behavior (P>0.05) with respect to the control treatment (peat). The behavior of papaya and passion fruit was similar (P>0.05), despite this, the germination in the three experiments was lower than that of the laboratory test. It is concluded that the raw material used as a substrate influences the nutrient content of the biochar, thus, the soil mix with 10% orange biochar is an optimal substrate for the production of tomato seedlings.
Keywords: biochar; nutrients; seedlings; nursery; fruit trees